EXPLANATORY ANALSIS ON EMERGENCY FUND FOR EMPLOYEE - Yenni Martok (Journal of Accounting and Management Innovation, 2023)
The purpose of this research is to analyze the importance of emergency fund for employee. This research is using library research. Every people need money to spend for the life expenses. There are lots of expenses that each person will have and different compared to others. Different age will face different needs and the level of saving will vary from one to another. Individual will have own income and also it will affect the level of saving and emergency fund. Emergency fund is cash that need to put aside for the events or activities that are outside our planning. It is one important issues for the financial planning in the long term. To prepare for the emergency fund then need to be carefully done accordingly. Because the need for the emergency, then there is no special purpose for this fund. Emergency fund need to be kept in the financial products that is liquid and can be converted to cash when it is needed. It does not necessary to save it in deposit only, but there are so many financial instruments as long as the protection for its safety and easier to converted to cash. Sometime people need to prepare before needs money for the urgent cases. Employee is someone who work for others. Employee received the income from the employer and usually it will receive at the end of the month. Sometimes it can be found that there are hardship times where it will lead to unemployment. The example is when Covid 19 attack for the local lockdown and affect the business scale. Business are slow down dramatically, laying off employees during a time where finding a new job will be problems for some people. Some employee will also lost household income if spouses or family members were being laid off. Because of some reasons, employee needs to prepare for emergency fund. Emergency fund is very important for individual including employee. Keyword : Emergency Fund, Employee